Build a large language model - Raschka, Sebastian (Manning Publications, 2024)
In Build a Large Language Model (from Scratch), you'll discover how LLMs work from the inside out. In this insightful book, bestselling author Sebastian Raschka guides you step by step through creating your own LLM, explaining each stage with clear text, diagrams, and examples. You'll go from the initial design and creation to pretraining on a general corpus, all the way to finetuning for specific tasks.
"In Video Editions the narrator reads the book while the content, figures, code listings, diagrams, and text appear on the screen. Like an audiobook that you can also watch as a video.". - Online resource; title from title details screen (O'Reilly, viewed August 5, 2024)
Keywords: Artificial intelligence; Natural language processing (Computer science); Intelligence artificielle; Traitement automatique des langues naturelles; artificial intelligence; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet